Inventory Exchange Web-Based Database a Feasibility Study - Ilagan, Gazel Antonette T. (College of Engineering, 2001)
A project feasibility study is conducted on the uploading of a database on the Internet. The database aims to facilitate the exchange of inventory excess between manufacturing companies within the Philippines. The database will be maintained by Inventory Exchange Center Philippines Inc. and will be called InEx Web-Based Database. The study will cover 10 years of operation of the company and will employ different methodologies to accomplish this. Different organizations, both government and private were consulted to gather pertinent data that will help arrive at the viability of the project. Also, laws regarding this type of business were researched to establish the legalities of such an operation. The operations via the Internet will commence by the start of year 2002. The target area of operations will be the National Capital Region for starters since this is where the demand is most attractive, but as seen from the study there is a very big room for expansion. In order to determine whether or not there is indeed a demand for such a service, a market survey is conducted through e-mail asking manufacturing companies whether or not they are interested with the kind of service InEx will be offering. The result from the survey establishes the demand for the project. Furthermore, supply via manpower and other service resources to meet the demand are determined and the level of service it requires. To push for the sale of the project, various marketing strategies will be employed to disseminate the information about the features of the database project. The database will be uploaded on the Internet making it available 24 hours a day and 7 days a week. Meaning there is a timely match-up of inventory excess for a more efficient and effective exchange. The database will off course be upgraded and updated regularly to ensure its integrity. Samples of the program/database will be provided for free to possible clients. Although the web-site will be accessible to all those who have internet access, the database need to be uploaded to the client network via the CD software that will be provided so that there will be a faster transaction. Once the system/program is already stored in the client's network, it will not solely rely on the website and the ISP's efficiency, hence encouraging faster exchange. Aside from the database exchange, there are also value-added service that the project will offer such as warehousing and trucking. From all of these, the company will charge a 10% service fee to its client. In effect, the company is a third party server between buyers and sellers of inventory excess. To further check the viability of the project, financial statements are projected for the first 20 years of operation of the company. Pro-forma income statements, cash flow projections, and pro-forma balance sheets are projected with the aid of the sales plan and service operations plan of the company. From these financial figures, different tests and measure are employed to conduct a financial analysis on the project. Other measures like the NPV, IRR, and MARR are applied to the project to test its profitability. A look into the organization of the proposed project is also conducted in order to determine the form of organization that will best answer the needs of the proposed project organization-wise, The positions with the organization are defied and qualifications per position are detailed. The compensation due for each position plus benefits is also set. Finally, a look into the socio-economic contribution of the project is done. Several contributions are stated, both quantitative contributions and qualitative contributions of the project to the society and the economy. Such a study is necessary especially when the commercial profitability of a project is not enough to justify its implementation. Since the project is very much capital intensive, a social profitability study will be most helpful to justify its implementation aside from the fact that it requires a large capital investment. From the findings from the different parts of the study, a conclusion about the operation will be delivered to access the conclusiveness and viability of the project as a whole.